Perceived media coverage and environmental awareness among university students in Malaysia : the moderating effects of perceived government role and green value - Fayyad, Khaled M.I. Abu (2017)
The inconsistent findings on the relationship between media coverage (MC) and environmental awareness (EA) provide the current study research gap which invites further investigation into the possible contingent variables (moderator). Based on the emerging theoretical framework, government role (GR) and perceived green values (GV) were postulate as potential moderators. Thus, a research framework was proposed to examine the relationship between MC and EA, as well as the moderating effects of GR and GV on the relationship. The research framework was underpinned by Agenda Setting Theory and Framing Theory, and further supplemented by Limited Effects Theory, and Institutional Theory. Proportionate random sampling was adopted along with survey method to obtain data. The questionnaires of 730 respondents were used for data analysis that employed Exploratory Factor Analysis and Confirmatory Partial Least Square Structural Equation Modelling analysis techniques. It was found that all direct associations between MC and EA, GV and EA, and GR and EA demonstrated significant results. Further, while GR was found significantly moderated the relationship between MC and EA, there was no evidence for significant moderating effect of GV. It was found that all direct associations between MC and EA, GV and EA, and GR and EA demonstrated significant results. Further, while GR was found significantly moderated the relationship between MC and EA, there was no evidence for significant moderating effect of GV.